Selected appendices of the history and culture of Samar from 1768-1898 - Cruikshank, Bruce
"The selected appendices from the book Samar: 1768-1898 will provide the avid researchers, historians and scholars with the authentic historical records and documents in digested form about the province of Samar within a span of 130 years."
Reprinted from the book SAMAR: 1768-1898 with permission from the author, Dr. Bruce Cruikshank, and the publisher, The Historical conservation Society, Inc. of Manila through Don Alfonso Felix, Jr.
Keywords: Waray culture; Samar -- Eastern Visayas